Exploring the relationship between social attachment and dopamine D2/3 receptor availability in the brains of healthy humans using [11C]-(+)-PHNO. (4th March 2017) - Caravaggio, Fernando; Chung, Jun Ku; Gerretsen, Philip; Fervaha, Gagan; Nakajima, Shinichiro; Plitman, Eric; Iwata, Yusuke; Wilson, Alan; Graff-Guerrero, Ariel
ABSTRACT: Differences in striatal dopamine (DA) function may be related to differences in the degree of social attachment to others. Using positron emission tomography (PET), socially detached persons demonstrate reduced DA D2/3 receptor (D2/3 R) availability in the striatum. However, previous PET studies have only used antagonist radiotracers for D2/3 R and have not specifically examined regions of interest (ROIs) such as the ventral striatum (VS). In 32 healthy persons, we investigated the relationship between self-reported attachment and DA D2/3 R availability in striatal and extrastriatal ROIs as measured using the agonist radiotracer [ 11 C]-(+)-PHNO. Surprisingly, more social attachment—as measured by the attachment subscale of the temperament and character inventory—was related to less [ 11 C]-(+)-PHNO binding in the VS ( r (30) = −.43, p  = .01). This relationship held in a subsample who also completed the detachment subscale of the Karolinska Scales of Personality ( r (10) = .62, p  = .03). However, no relationships were observed with BPND in the dorsal striatum or D3 R-specific ROIs. One potential explanation for these findings is that persons who are more socially detached have less endogenous DA occupying D2/3 R in the VS. This interpretation warrants investigation by future research. These findings may help us better understand the neurochemical basis of attachment.